Effect of a Chess Training Program on the Development of the Executive Functions in Primary School - Marc Baig; Carles Rostan; Carme Saurina (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
Executive functions are higher cognitive abilities that allow the control of behaviour, cognition, and emotions. The present study analyses if a chess training program helps to develop the executive functions, and if these improvements are transferable to activities in daily life. To accomplish this purpose a quasi-experimental approach was designed. Two groups of children aged between 8 and 12 years were compared. The experimental group attended a chess workshop. The control group attended another educational workshop with the same frequency and duration as the experimental group. The BRIEF-2 test was applied to both groups, families and teachers of the boys and girls before and after the workshops. The results showed that the children in the experimental group improved in the executive functions evaluated by teacher perception but not by parental perception, and the control group did not present any relevant significant improvement. In the discussion, we comment on these results.